2015
DOI: 10.5762/kais.2015.16.9.6036
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Emotional intelligence, Academic self-efficacy and self-leadership among Nursing Students

Abstract: The purpose of this study was to identify the relationship between emotional intelligence, academic self-efficacy, and self-leadership among nursing students. Subjects were 230 nursing students in South Korea . Data were collected using self-report questionnaires from September 1 to 30, 2015, and analyzed using frequencies, t-tests, ANOVA, Pearson's correlation, and multiple regression using SPSS Win 18.0. Self-leadership was significantly positively correlated with emotional intelligence and academic self-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The result of significantly lower academic resilience among participants with high levels of stress from school life and those who were dissatisfied with their academic major was similar to that of a preceding study ( 30 ). Academic stress and dissatisfaction have been shown to negatively impact academic satisfaction, specifically online studies ( 31 ), and thereby causing academic failure.…”
Section: Discussionsupporting
confidence: 74%
“…The result of significantly lower academic resilience among participants with high levels of stress from school life and those who were dissatisfied with their academic major was similar to that of a preceding study ( 30 ). Academic stress and dissatisfaction have been shown to negatively impact academic satisfaction, specifically online studies ( 31 ), and thereby causing academic failure.…”
Section: Discussionsupporting
confidence: 74%
“…The level of adaptation to college life among nursing students had significant positive correlations with learning commitment, self‐efficacy and grit. Previous studies demonstrated that the higher the learning commitment (Lee et al, 2020), self‐efficacy (Lee, Lee, & Kwak, 2021) and grit (Lee, Gwon, et al, 2021; Lee & Park, 2018), the higher the level of adaptation to college life. These results reflect the outcomes of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Nursing college students with high learning commitment, who are experiencing mixed learning methods with non‐face‐to‐face online teaching, show higher levels of academic achievement, adaptation to college life and satisfaction (Chin & Jung, 2020; Lee et al, 2020). Self‐efficacy, an intrinsic factor that makes this learning commitment possible, refers to the confidence necessary to achieve individual goals and is an important factor for reinforcing academic motivation and increasing flexible thinking to adapt well to college life (Cho & Park, 2018; Lee, Lee, & Kwak, 2021b). High self‐efficacy among nursing students facing non‐face‐to‐face online learning situations that are being wholly or partially conducted due to the prolonged COVID‐19 pandemic, is expected to facilitate adaptation to college life through effective learning performance and successful management of learning outcomes (Kim, Kim, & Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the direct effect of mindful agency is higher than the mediating effect to a large extent, and mindful agency may promote self-leadership through other ways. In addition to metacognitive ability, other mediating variables may also influence the relationship between mindful agency and self-leadership, such as the influence of emotional intelligence and self-efficacy on self-leadership ( Lee, 2015 ). In the future research, it is necessary to explore other mediating variables to more comprehensively reveal the internal influencing mechanism of mindful agency on self-leadership.…”
Section: Discussionmentioning
confidence: 99%